Method for preparing sulfenamide thiofide by catalyzing oxidization of molecular oxygen in water phase - NIU GUANGWEN; DING JUNJIE; SONG FENGCHAO; WANG FEI; LI HONGXI; GE TONGWEI; GUO TONGXIN; WANG ZHIQIANG; YANG LITING; YIN YUENING; YANG GUANYU; DOU YINGCHAO; et al. (2017)
The invention relates to a method for preparing sulfenamide thiofide by catalyzing oxidation of molecular oxygen in a water phase. According to the method, a water-soluble transition metal phthalocyanine compound is utilized as a catalyst, and 2-mercaptobenzothiazole generates oxidation cross coupling reaction with amine (tert-butylamine or cyclohexane) for 1 to 30 hours to generate sulfenamide thiofide in the water phase under the conditions that oxygen (or air) pressure is 0,01 to 1MPa, and temperature is 40 to 100 DEG C. Reaction of the preparation method disclosed by the invention is performed in the water phase, other organic solvents are prevented from being added, catalyst activity is high, reaction efficiency is high, the catalyst can be used repeatedly, a synthesizing technology is concise, product selectivity is high, by products are few, waste is little, environmental friendliness is achieved, and the preparation method has stronger industrial application prospect. 本发明涉及种催化分子氧氧化制备次磺酰胺类橡胶促进剂的方法，该方法以